Influence of iron-deficient diets during gestation and lactation on cerebral fatty acids and eicosanoids in guinea pig offspring—Comparison of studies with different sources of dietary lipids. (October 2019) - Jougleux, Jean-Luc; Rioux, France M.; Fiset, Sylvain; Boudreau, Luc H.; Surette, Marc E.
Highlights: We previously showed that mild iron deficiency anaemia (IDA) during pregnancy and lactation in guinea pigs alters the auditory functions of the offspring. In previous studies the effect of IDA on the auditory functions in 24-day old offspring differed based on the source of dietary lipids during pregnancy and lactation. Mild iron deficiency anaemia (IDA) during pregnancy and lactation impacts on encephalum fatty acid composition and prostaglandin content in 24-day old offspring. Studies of IDA during prenatal development should consider dietary lipid compositions. Abstract: Previous studies showed that mild iron deficiency anaemia (IDA) induced by feeding an iron deficient (ID) diet to female guinea pigs during gestation and lactation to alters the auditory functions of the offspring when corn oil is the only source of dietary lipids. Conversely, feeding an ID diet with a dietary fatty acid composition similar to that of typical human western diets induced minor impairments. Since tissue fatty acid metabolism is affected by dietary iron, the current study measured the impacts of these ID diets (ID-corn and ID-west) compared to the corresponding iron-sufficient control diets (IS-corn and IS-west) on encephalum fatty acid metabolism in the offspring at post-natal day 24. IDA induced by the ID-corn diet resulted in significant increases in encephalum n-6 PUFA content, but IDA induced by the ID-west diet had little impact on fatty acid profiles compared to the IS-west group. Brain COX II protein expression and FADS2 mRNA expression were statistically unaffected in both experiments, but encephalum PGE2 concentrations were significantly reduced in ID-west pups. These results suggest IDA studies during prenatal development should consider dietary lipid compositions.